Successful repair of recurrent rectovaginal fistula by stratified suture using transanal endoscopic microsurgery: A CARE-compliant case report. Issue 36 (September 2016) - Chen, Weijie; Chen, Xin; Lin, Guole; Qiu, Huizhong
Abstract: Background: Rectovaginal fistulas (RVFs) are abnormal connections between the rectum and vagina. Although many surgical approaches to correct them have been attempted, management of RVFs still remains a challenge, especially for recurrent RVFs. Methods: In the present study, we report a case in a 22-year-old female with a chief complaint of obvious passages of flatus or stool through the vagina for 10 years. She had suffered a vaginal trauma from a violent accident 10 years prior, and gradually noticed the uncontrollable passage of gas or feces from the vagina 2 weeks later. The patient underwent a transvaginal direct repair surgery at local hospital 9 years ago, but the symptoms recurred 1 month after the surgery. After 2-years monitoring, the patient underwent another transvaginal repair surgery (fistulectomy followed by direct suture) at another hospital, but the fistula recurred again. We initially performed a temporary protective transversostomy upon admission. After 8-months of observation, a methylene blue test was conducted and the diagnosis of recurrent RVF was confirmed. Subsequently, we performed a successful repair by stratified suture using transanal endoscopic microsurgery (TEM). The scar tissue on the posterior wall of the vagina and the anterior wall of the rectum were meticulously excised until the margin of the excisional line showed healthy tissue. In addition, the fistulous tract was completely removed. The edges of the fistula on the posterior wall of the vagina were closed by simple continuous suturing, and the rectal anterior wall was sutured in the same manner. Results: During a 1-year follow-up period, the fistulae were not recurrent and no complication such as incontinences or rectal bleeding were found. The latest Wexner score was 3. Conclusion: We present a case of successful treatment with stratified suture using TEM throughout the procedure. We strongly recommend this efficient and minimally invasive procedure for recurrent RVFs.